Investigation of practices to support the complex communication needs of children with hearing impairment and cerebral palsy in a rural district of Kenya: a case series. Issue 6 (1st August 2013) - Bunning, Karen; Gona, Joseph K.; Buell, Susan; Newton, Charles R.; Hartley, Sally
Abstract: Background: Rehabilitation services are scarce in low‐income countries, where under‐representation of some specialist professions has led to the role extension of others. An example of this can be found in Kilifi in Kenya where the role of speech and language therapy has been taken on by occupational therapists and teachers. Aims: To investigate the communication practices used by these professional groups to support children with complex communication needs in a rural part of Kenya and to explore the ways in which this might be seen to facilitate or obstruct improved communication by asking the following questions: What are the critical features of interactional discourse in practitioner–child dyads with caregiver–child dyads providing a natural comparison? What communicative modalities and practice techniques are invoked? And how does this information relate to extending professional roles? Methods & Procedures: An in‐depth, descriptive study of a case series was conducted in a school for deaf children and the occupational therapy department of a district general hospital. A mixed methodology was used involving naturalistic observation and applied linguistics analysis. A convenience sample was established comprising six practitioner–child dyads assigned to partnership types: (A) three children with hearing impairment and their teachers; and (B) three children with cerebral palsy and their occupational therapists. As a natural comparator, the same three children in B were also observed with their mothers (partnership type C). Dyadic interaction was video recorded on three occasions. The video data were sampled, transcribed into standard orthography and translated. Codes were applied to determine turn structure, linguistic move types and communicative modalities. Sequential analysis was conducted on the move types. Outcomes & Results: Partnership type A dyads showed a fairly even turn distribution between teacher and child. A common pattern was teacher‐initiated Instruct and Model/Prompt, followed by child response in the form of an Action . The most frequently used modality was Sound Production a nd Hands‐on‐Articulators, which corresponded to articulation drill practice. Partnership type B dyads revealed a tendency towards adult domination of turns. The majority of adult‐initiated moves required no response from the child. The practice technique Hands‐on‐Articulators involved manipulating the oral musculature of the child. Partnership type C dyads showed resonances of type B dyads, although focused more on Motor‐Action in relation to task performance. Conclusions & Implications: The assignment of speech and language therapy duties to teachers and occupational therapists has resulted in suboptimal practice for children with complex communication needs.